Un análisis de los personajes de Eva Luna desde una perspectiva feminista - Wilson, Sydney Marie (East Carolina University, 2023)
The purpose of this thesis is to analyze Isabel Allende's novel Eva Luna, and the respective characters from an intersectional feminist perspective. The first chapter will analyze the eponymous protagonist of the novel, Eva Luna. This section will focus on examining the common themes and subgenres frequently attributed to the novel and this character through a feminist lens. More specifically, this section will analyze the use of picaresque and Bildungsroman literary elements to amplify the feminist message of the novel. The second chapter will focus on an important secondary character Mimi, previously known as Melecio, and analyze the presence of a trans woman as a leading character in a major Latin American novel. The third and final chapter of this thesis will center around the primary masculine characters of the novel: Huberto Naranjo, Riad Halabi, and Rolf Karle. The analysis of these characters will focus on the idea of machismo and the spectrum of "machismo-feminismo" seen within various Latin American societies through the lens of hegemonic masculinity.
Keywords: Queer Theory; Allende, Isabel. Eva Luna; Feminism in literature; Transgender people in literature; Women authors, Chilean